Targeting Neurodegeneration in Alzheimer’s Disease Using Natural Products Derived from Maya Traditional Medicine - Taylor, Matthew W (Université d'Ottawa / University of Ottawa, 2014)
Alzheimer’s disease (AD) is a complex neurodegenerative disorder with limited treatment options. Previous research has shown that metabolism of the platelet activating factor (PAF) family of lipid second messengers is impaired in AD. While PAFs are known to exacerbate glutamate excitotoxicity, signal tau hyperphosphorylation, and mediate amyloid β neurotoxicity, it is not yet clear whether cognitive decline can be ascribed to activation of the G-protein-coupled PAF receptor (PAFR). Here, I assessed whether loss of PAFR would alter Morris water maze performance in the TgCRND8 (Tg) mouse model of AD. I show that learning is impaired in Tg PAFR+/+ but not in Tg PAFR-/- mice. Together, these findings suggested that blocking PAFR-mediated glutamate overload or inhibiting PAF-synthesizing enzymes are two relevant therapeutic strategies. As traditional medicine is a major form of health care in regions like Mesoamerica, I conducted an ethnobotanical survey of medicinal plants used by Q’eqchi’ Maya healers of southern Belize to treat symptoms relevant to AD. I collected a total of 22 plants, 19 of which were identified to the species level. None of the plant extracts used for symptoms of AD were neurotoxic when tested on cerebellar granule neurons (CGNs). I found that extracts of Margraviaceae gentlei and Gonzalagunia panamensis protected CGNs from glutamate-induced excitotoxicity, in vitro, and Peperomia hirta inhibited sPLA2 activity. These results demonstrate a pharmacological basis for Q’eqchi’ Maya traditional medicine used to treat symptoms relevant to AD, and highlight several plants with potential for future development into natural products for the treatment of AD.
Keywords: Alzheimer's disease; Ethnobotany; Maya; Neurodegeneration; Traditional medicine; Platelet activating factor; Platelet activating factor receptor; Excitotoxicity; Phospholipase A2; Dementia